GNSS Signal Labeling, Classification, and Positioning in Urban Scenes Based on PSO-LGBM-WLS Algorithm - Luo, Hui; Liu, Ji; He, Di (IEEE transactions on instrumentation and measurement, 2023)
In urban canyon areas, the receiver positioning error of the global navigation satellite system (GNSS) is mainly affected by multipath (MP) effects and nonline-of-sight (NLOS) reception, especially NLOS reception issues, which sometimes even cause errors of hundreds of meters. Therefore, detecting and suppressing NLOS reception has become an effective means to improve the positioning accuracy of GNSS, which has been extensively researched and used in the literature. Based on the preferred combination of satellite signal features, a line-of-sight (LOS)/NLOS signal classification method utilizing the light gradient boosting machine (LGBM) is first proposed in this article. And based on this, while calculating the position coordinates by combining the weighted least squares (WLS) algorithm and the particle swarm optimization (PSO) algorithm, the reception of NLOS can be suppressed so that its influence can be significantly reduced, and finally, a novel PSO-LGBM-WLS algorithm model is established in this study. In addition, in view of the difficulty of obtaining labels in NLOS detection using machine learning-based algorithms, we also propose to use the pseudorange error as the basis for label production and use PSO to optimize the classification threshold of pseudorange error, which also helps to reduce the final positioning error from another aspect. In the real experiments, relying on the data collected by the Google team in the San Francisco area, the proposed algorithm model is tested in terms of LOS/NLOS signal classification and positioning accuracy, which are compared with other machine learning models and positioning methods. The experimental results show that the proposed algorithm has the advantages of high classification accuracy and short consumption time, which provides the possibility for practical application. From the positioning results, the proposed PSO-LGBM-WLS algorithm model shows significant effects on improving positioning accuracy by detecting and suppressing NLOS reception.